Balsam-pear-like rutile/anatase core/shell titania nanorod arrays for photoelectrochemical water splitting. (20th October 2017) - Wen, Wei; Yao, Jin-Cheng; Gu, Yi-Jie; Sun, Tu-Lai; Tian, He; Zhou, Qi-Lai; Wu, Jin-Ming
Abstract: In this work, a solution combustion followed by dissolution in hydrogen peroxide is adopted to achieve a precursor for decorating anatase TiO2 nanosheets along single-crystalline rutile TiO2 nanorods, which achieves balsam-pear-like core/shell nanorod arrays with enhanced photoelectrochemical water splitting. The enhanced photoelectrochemical performance is attributed to the novel nanoarchitecture, which can simultaneously offer a high surface area, enhanced light-harvesting, a rutile/anatase junction for charge carrier separation and a conductive pathway for charge carrier collection. The photoanode design can also give hints to other functional materials.